2022
DOI: 10.1080/10717544.2022.2081383
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the anti-inflammatory effect of self-assembled hybrid lecithin–chitosan nanoparticles via hybridization with gold nanoparticles for the treatment of psoriasis: elemental mapping and in vivo modeling

Abstract: Gold nanoparticles are a promising drug delivery system for treatment of inflammatory skin conditions, including psoriasis, due to their small size and anti-inflammatory properties. The aim of this study was to conjugate gold nanoparticles with anti-psoriatic formulations that previously showed successful results in the treatment of psoriasis (tacrolimus-loaded chitosan nanoparticles and lecithin–chitosan nanoparticles) by virtue of their surface charges, then examine whether the hybridization with gold nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Proper choice of the type of nano-system plays an important role in their interaction with the skin. It is evident that polymeric nanoparticles, especially those having a particle size less than 100 nm and carrying a charge, are an excellent choice for the treatment of inflammatory skin disorders due to the selective accumulation in the inflamed skin [ 136 , 137 , 138 ]. On the other side, lipidic systems such as lipid nanoemulsions and nanocapsules tend to enhance the transdermal permeation of the encapsulated drugs due to their greater ability to diffuse through the different skin layers [ 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proper choice of the type of nano-system plays an important role in their interaction with the skin. It is evident that polymeric nanoparticles, especially those having a particle size less than 100 nm and carrying a charge, are an excellent choice for the treatment of inflammatory skin disorders due to the selective accumulation in the inflamed skin [ 136 , 137 , 138 ]. On the other side, lipidic systems such as lipid nanoemulsions and nanocapsules tend to enhance the transdermal permeation of the encapsulated drugs due to their greater ability to diffuse through the different skin layers [ 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prepared nanoparticles (CNB-PLGA-PSar-NPs) were measured using DelsaNano C (Beckman Coulter, USA) for particle size, polydispersity index (PDI), and zeta potential ( 29 31 ). Photon correlation spectroscopy is the name of the fundamental concept behind this instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to bare hybrid nanoparticles, our study found significant differences in some inflammatory markers. Furthermore, these gold conjugates demonstrated an anti-inflammatory effect, as evidenced by a lower spleen/body weight ratio and better histopathological skin condition compared to other preparations investigated [ 178 ].…”
Section: Current Nanotechnology-based Approaches For the Topical Trea...mentioning
confidence: 99%